Microstructural and Dielectric Properties of (Ba,Nb)(Ti,Cu)O₃-(BNTC) and (Ba,Nb)(Ti,Sn)O₃-(BNTS) Ceramics - Keophilavong, Somsathith (2003)
Microstructural and dielectric studies of (Ba1-xNbx)(Ti1-xl2Cuxl2)03 and (Ba1-xNbx)(Ti1-xl2Snxl2)03 prepared by solid-state reaction route were investigated . The compositions with varying x in those systems were prepared by standard powder processing techniques. The two systems were based on the reaction between BaC03, N b205, Ti02 and CuO to form (Ba,Nb)(Ti,Cu)03 (BNTC) and the other system is the reaction between BaC03, Nb205, Ti02 and Sn02 to form (Ba,Nb)(Ti,S n)03(BNTS). These ceramics compounds are of commercial importance as ceramic capacitors and there is also scientific interest since it provides a straightforward example of the effect of solid solution composition of ceramics on dielectric properties. This thesis reports the detailed investigation with respect to the above mentioned compositions. The variation of microstructure with sintering temperature and soaking time at each sintering temperature, and that in the capacitance and resistance of each of the sample has been examined .